Assessment of Biotransformation of Sludge from Vegetable Oil Refining by Composting. Issue 2 (3rd April 2017) - Lahsaini, Slimane; Aguelmous, Anas; El Fels, Loubna; Idrissi, Leila; Souabi, Salah; Zamama, Mohamed; Hafidi, Mohamed
ABSTRACT: The evolution of organic matter of sludge from vegetable oil refining (50%) mixed with turf (40%) and straw (10%) during 6 months of composting was evaluated by physicochemical and spectroscopy analysis. The intense microbial activity is characterized by a significant increase in temperature (over 67°C) during the thermophilic phase (7 days). The final product is characterized by a decomposition rate of 50, C/N ratio about 12, NH4 + /NO3 − ratio less than 1, and a neutral pH. The lipid analysis showed that total lipids decreased by 83% as a result of biodegradation of lipid compounds of the composted substrate. The degree of polymerization during composting is of about 16%, which provides information on the success of the process. The spectroscopic analysis showed a decrease of the ratios E4/E6 and E2/E6, which clearly shows the humification of organic matter. The physicochemical and spectroscopy parameters of the mixture show the stability and maturity of the final compost, which is confirmed by the germination index (60% for lettuce and turnips, and 90% for cress and lucerna). The results of the evolution of sludge from vegetable oil refining mixed with green wastes produced a mature product that can be applied in agriculture.